Analisis Pengaruh Transformational Leadership, Work Environment, Reward and Recognition dan Job Satisfaction terhadap Employee Performance XYZ E-Commerce - Putri, Desyanti Tarida; Wanasida, Albert Surya (Cv. Syntax Corporation Indonesia, 2025)
Digitalization brings many changes to business aspects, including digital companies themselves. Current technological developments have brought quite a lot of efficiency to the aspect of work performance, the need for quality human resources is increasing. This study examines the effect of transformational leadership, work environment, reward and recognition and job satisfaction on employee performance in employees working at XYZ e-commerce. This study was conducted quantitatively on 146 XYZ e-commerce employees in the marketplace section, where samples were taken using simple random sampling techniques. The analysis was carried out using PLS-SEM. The results showed that transformational leadership, work environment, and reward and recognition have a positive effect on employee satisfaction. Therefore, companies need to improve transformational leadership, work environment, and reward and recognition so that job satisfaction and employee performance can be improved. This study concludes that strengthening transformational leadership styles and fair reward systems and a conducive work environment can improve employee satisfaction and performance. The implication is that XYZ e-commerce management needs to adjust its HR management strategy that is oriented towards employee motivation, welfare, and productivity to maintain the company's competitiveness in the digital era.